(untitled) (Research, Society and Development, 2022)
Introduction: The COVID-19 pandemic impacted the Management of Hospital Services, as well as the performance and role of leaders in the face of this new epidemic. Objective: to assess the prevalence of factors associated with the leadership role of hospital managers before and during the COVID-19 pandemic. Methodology: The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) databases. and EBSCO Information Services, in March 2022. Results and discussion: COVID-19 evidenced a global crisis, requiring a transformation in the structure and work process of health units, highlighting the need for good planning for the face this epidemic advent. The research highlights the fundamental role of leadership in management to obtain good results: the hospital administrator must be assertive in decision-making and have good internal and external communication. In addition to training in the use of PPE, due to patients with severe and variable conditions, the assistance provided has become more complex, requiring knowledge that was not so required before, such as intubation, cricothyroidotomy and physical recovery processes, with managers responsible for the training of professionals. Final considerations: It is concluded that, far beyond routine actions, it is necessary to have specialized training, innovative vision and willingness to face potential challenges and abrupt adaptations, in the face of epidemic and pandemic episodes.